Exploring the mechanism of traditional Chinese medicine in regulating gut-derived 5-HT for osteoporosis treatment - Sun, Kai; Wang, Yincang; Du, Jiazhe; Wang, Yujie; Liu, Bo; Li, Xiaodong; Zhang, Xiaofeng; Xu, Xilin (Frontiers in Endocrinology, 2023)
Osteoporosis is a systemic bone disease characterized by an imbalance in the relationship between osteoblasts, osteocytes, and osteoclasts.This imbalance in bone metabolism results in the destruction of the bone's microstructure and an increase in bone brittleness, thereby increasing the risk of fractures.Osteoporosis has complex causes, one of which is related to the dysregulation of 5-hydroxytryptamine, a neurotransmitter closely associated with bone tissue metabolism.Dysregulation of 5-HT directly or indirectly promotes the occurrence and development of osteoporosis.This paper aims to discuss the regulation of 5-HT by Traditional Chinese Medicine and its impact on bone metabolism, as well as the underlying mechanism of action.The results of this study demonstrate that Traditional Chinese Medicine has the ability to regulate 5-HT, thereby modulating bone metabolism and improving bone loss.These findings provide valuable insights for future osteoporosis treatment.